Germanium-silicon alloy and core–shell nanocrystals by gas phase synthesis1. Issue 12 (28th March 2015) - Mehringer, Christian; Kloner, Christian; Butz, Benjamin; Winter, Benjamin; Spiecker, Erdmann; Peukert, Wolfgang
<x xml:space="preserve">Abstract</x> In this work we present a novel route to synthesize well defined germanium-silicon alloy (GexSi1−x) and core–shell nanocrystals (NCs) employing monosilane (SiH4) and monogermane (GeH4) as precursors in a continuously operated two-stage hot-wall aerosol reactor setup.